Yoga anatomy - Kaminoff, Leslie, 1958- (Human Kinetics, Inc., 2022)
"The book details the key anatomical systems involved in the practice of yoga, including the skeletal system, muscular system, respiratory system, and nervous system. Anatomical detail and explanation are blended with yogic breathing and mindfulness to create a complete yoga practice. Chapters detail standing, sitting, kneeling, supine, prone, and arm supported poses, or asana, with extensive anatomical illustrations and pose outlines. Cueing callouts connect movement to breath and highlight key aspects of practice"--Résumé de l'éditeur